EDUCATING ON STUNTING PREVENTION IN PREGNANT WOMEN WITH FLIPCHART MEDIA - Umaroh, Ayu Khoirotul; Firmansyah, F; Kussudyarsana, K; Berliana, Rahma Novita; Puspitasari, Anita; Mulyono, Afieina Maulida (Prosiding University Research Colloquium, 2024)
During pregnancy, pregnant women can make efforts to prevent stunting. Improvement of nutrition and health of pregnant women is closely related to the level of knowledge about meeting nutritional needs during pregnancy. Inadequate knowledge is an obstacle to improved nutrition. This community service aims to increase the knowledge of mothers about stunting prevention during pregnancy. The methods carried out are preparation, implementation of counseling using flipchart media in pregnant women's classes, and evaluation using pre and posttest questionnaires. The results of community service showed an increase in the average score of knowledge of pregnant women related to stunting prevention from 91.05 to 97.37. This increase in knowledge is faced with an impact on improving stunting prevention behavior.